HUBUNGAN JENIS KELUARGA BERENCANA (KB) SUNTIK DENGAN GANGGUAN MENSTRUASI PADA AKSEPTOR KB SUNTIK DI BIDAN PRAKTEK SWASTA (BPS) SUHARTINI KARANGANYAR KEBUMEN - Hapsari, Reni; yatun, Herni; Indrayani, Eni (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
The high morbidity rate in Indonesia is one of the major problemsthat requires special attention from the government. One of the concreteprogram to overcome the high morbidity rate issued by the government isfamily planning program. Contraception usage is a way or attempt toprevent a meeting between the mature egg cell with sperm cells inside theuterus that can cause pregnancy.The study is aimed to find out the correlation between one andthree monthly injection family planning acceptors with the menstrualdisorders in Suhartini Midwifery Clinic in Karanganyar Kebumen in2010. This study used descriptive correlation design with cross sectionalapproach with one and three monthly injection family planning acceptorsas the independent variable and menstrual disorders as the dependentvariable. There were 88 injection family planning acceptors taken as thesamples. The data were collected by questionnaires. The data wereanalyzed by using Chi-Square correlation formula.One monthly injection family planning acceptors in SuhartiniMidwifery Clinic did not experience menstrual disorders, (2). Threemonthly injection family planning acceptors in Suhartini Midwifery Clinicexperienced menstrual disorders, (3) there was a significant one andthree monthly injection family planning acceptors with the menstrualdisorders in Suhartini Midwifery Clinic in Karanganyar Kebumen in 2010with the acquisition value of Chi Square 76.766 and Asymp.Sig. (P-Value)0.000.Keywords: One and three monthly injection family planning acceptors,menstrual disorder